The existence of Malaqbiq Tau Mandar local culture to empower students' educational character - Nurhikma Ramadhana; Mimien Henie Irawati Al Muhdhar; Sulistijiono Sulistijiono (Jurnal Cakrawala Pendidikan, 2023)
Various studies and facts show that a developed nation is a nation whose character is strong. The integration of local wisdom culture is important to be developed into learning materials because it has a high potential to be utilized in developing the character of students. West Sulawesi Province can be one example. Mandar people living in the province have various cultures and philosophies of cultural diversity which are called the "Malaqbiq Tau Mandar". It is a cultural role model and a moral principle for the Mandar people of West Sulawesi. However, as time goes by, the cultural character of Malaqbiq Tau Mandar tends to be neglected, especially in the learning process in class. This can be seen in the lack of students. Therefore, this study aims to explore the character education values of Malaqbiq Tau Mandar as the basis to develop student character building at the University of West Sulawesi. This study was designed as a qualitative study using an ethnopedagogical approach. Data collection was carried out through interviews, observation, and documentation. Then, the data were analyzed through data reduction, data display, and conclusions. From the results of the study, it was revealed that the Malaqbiq Tau Mandar culture contains the following educational values: Malaqbiq pau. Second, Malaqbiq kedzo. Third, Malaqbiq sipaq, and fourth, Malaqbiq gauq (having a good spiritual level and good behavior or morals). In conclusion, Malaqbiq Tau Mandar's (MTM) character culture plays an important role in character education. Therefore, its good values should be integrated into the learning process to improve student character.